Implantation Cyst – A Rare Occurrence after Strabismus Surgery - Mahathi Vankireddi; Divya Bhargavi Katta; Sowjanya Yerra (Delhi Journal of Ophthalmology)
A conjunctival epithelial cyst is a rare occurrence poststrabismus surgery, with incidence ranging from 0.25% to 0.4%. This can occur when the conjunctival wound is not closed meticulously. Conjunctival epithelial cells buried beneath the conjunctival surface multiply over time creating a retention cyst. Risk factors include recessions, fornix incisions, and simple apposition of the conjunctival wound without sutures. When left untreated these cysts can enlarge and result in complications such as limitation of ocular movements, proptosis, and compression of ocular structures. This rare occurrence is underreported, and no specific management protocols have been established. Hereby, we present a case of implantation cyst developed after squint surgery. Despite meticulous surgical procedure, a retention cyst developed within 1 month of surgery. Cyst excision in toto with cauterization of the base was performed to avoid any recurrences. This case describes a rare complication of strabismus surgery and its management.